2015
DOI: 10.3109/10837450.2015.1022791
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and evaluation of pluronic lecithin organogels as a transdermal delivery vehicle for sinomenine

Abstract: The purpose of the present study was to prepare and optimize sinomenine (SIN) pluronic lecithin organogels system (PLO), and to evaluate the permeability of the optimized PLO in vitro and in vivo. Box-Behnken design was used to optimize the PLO and the optimized formulation was pluronic F127 of 19.61%, lecithin of 3.60% and SIN of 1.27%. The formulation was evaluated its skin permeation and drug deposition both in vitro and in vivo compared with gel. Permeation and deposition studies of PLO were carried out wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Thus, the percent cumulative amount of drug release was reduced, as the viscosity of the formulations increased and these results were in accordance with earlier study findings (Pandey et al, 2010). The gelation temperature range of our formulations lies below normal body temperature because our formulation exists in gel state and similar findings were also reported by Ba et al (2016). The skin irritation study was also performed on rats and all formulations showed no detectable sign of skin irritation, indicating excellent compatibility with skin.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the percent cumulative amount of drug release was reduced, as the viscosity of the formulations increased and these results were in accordance with earlier study findings (Pandey et al, 2010). The gelation temperature range of our formulations lies below normal body temperature because our formulation exists in gel state and similar findings were also reported by Ba et al (2016). The skin irritation study was also performed on rats and all formulations showed no detectable sign of skin irritation, indicating excellent compatibility with skin.…”
Section: Discussionsupporting
confidence: 80%
“…These tests demonstrated that SH-DM has enough mechanical strength to create pores for drug penetrating into skin. [52][53][54] . Cumulative permeation quantity of SH from SH-G and SH-DM was determined via the in vitro permeation study (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The sample was analyzed to determine the drug content by HPLC at 254 nm. The release kinetics of the formulations were calculated, and release patterns for those formulation were analyzed using three mathematical models: -(a) zero order kineticsreleased amount per unit area (mg/cm 2 ) against the time (h), (b) Higuchi kineticsreleased amount per unit area (mg/cm 2 ) against the square root of time (h) and (c) first order kineticslog of released amount per unit area (mg/cm 2 ) against the time (h) 9,47 .…”
Section: In-vitro Drug Release Studymentioning
confidence: 99%